Sicilian Theatres with Paraskenia Scene Buildings: An Updated Framework for their Chronological Integration - Panagiotonakou, Maria (Journal of Greek Archaeology, 2021)
Hellenistic theatre in Magna Graecia and Sicily differs in morphology from its contemporaries in Greece and Asia Minor. Since the beginning of the previous century, scholars have developed a discussion on a variety of issues in their attempt to better understand the architectural evolution of the Sicilian stone theatres, and in particular of their scene building. The most apparent and persistent problems lie in the uncertainty of dating and the morphology of each of the scene buildings. That is due to various difficulties that will be discussed further into this article. Over the last 100 years, this broad discussion has led to very different conclusions and interpretive proposals, especially regarding the dating of the original construction, the identification of the various building phases of these theatres, and the reconstruction proposals for their scene buildings. The issue of dating is related to the issue of the Romanization of Sicily and so far, it has been one of the most problematic chapters in the history of the island. Researchers evaluate differently both archaeological finds and historical sources, thus resulting in divergent interpretations of the significance of this period in the history of Sicily.